Protestos no Brasil: pós-modernidade e midialivrismo com os #jornalistaslivres e #mídianinja - Silva, Adelino Pereira da (2017)
Cyberculture has caused changes in communication processes in the contemporary world, especially in relation to the poles of information production and diffusion, giving significant visibility to free media and post-mass movements, aided by the communication established through portable devices, (Wi-Fi, 3G, 4G) and other digital tools such as social networking sites as well as streaming and collaborative platforms. This new media communication phenomenon, with P2P communication, carries hybrid, convergent and multimedia elements, through which the subjects carry out new media practices and, in this way, put in tension the relations of power in the mediatic ecosystem by acting in Postmodernity post-mass movements, such as midialivrism. In order to understand how this phenomenon occurs, we analyze the configuration of midialivrism (MALINI; ANTOUN, 2013) in a convergent way to social manifestations that have occurred in Brazil since 2013, with the free collectives Mídia NINJA and Jornalistas Livres (Free Journalists), also converging to cyberculture, ruled by the cyberculture laws (LEMOS, 2003). These collectives emerge from this scenario, which mixes cyber-presence activism, providing the basis for reflecting on the points of tension and connection between free-media practices and corporate media, pointing to post-journalism. From the participant observer method, and with the aid of the grounded theory (DIC, 2005), we collect and analyze the material produced by midialivists in cyberculture. Through analysis and interpretation, it resulted in a mapping of a set of midialivist practices. This path made it easier to identify the midialivist's activities in the internet and street networks, and how the three factors (consumption / sharing / production) conditioned each other, ended up connecting, in a demonstration of what this new relationship of free media with Journalism as an alternative media in the mediatized society and how it interacts, in a collaborative way, on the social protest and movements.